A randomized, comparative study of supervised and unsupervised artesunate-amodiaquine, for the treatment of uncomplicated malaria in Ghana. - Oduro, A.R.; Anyorigiya, T.; Anto, F.; Amenga-Etego, L.; Ansah, N.A.; Atobrah, P.; Ansah, P.; Koram, K.A.; Hodgson, A. (My University, 2008)
Although the use of artesunate-amodiaquine treatment is growing in Africa, data on its effectiveness are limited. In only the second published comparison of supervised and unsupervised treatments with this combination, Ghanaian children with uncomplicated malaria have recently been investigated in an open-label, randomized, comparative study. Children aged 6-120 months attending the Navrongo War Memorial hospital between November 2005 and December 2006 were enrolled if they had uncomplicated Plasmodium falciparum malaria and at least one of their parents/guardians gave their informed consent. Overall, 638 patients were screened, 357 were found to have P. falciparum infection, and 308 of these satisfied the other selection criteria and were enrolled. The subjects were divided randomly into two treatment arms. All the children were scheduled to receive 10 mg amodiaquine/kg and 4 mg artesunate/kg daily for 3 days but only 154 (the 'supervised') were given all their treatments in hospital, with each dose directly observed. Although the other 154 children (the 'unsupervised') were given their first dose in hospital, under supervision, they were then sent home with the tablets they required to complete treatment. Study participation lasted for 28 days, with follow-up on days 3, 7, 14, 21 and 28. During follow-up, axillary temperatures, any emergent signs and symptoms, and concomitant drug consumption were recorded and haemoglobin concentrations and malarial parasitaemias and gametocytaemias were measured. All but seven of the 308 subjects completed the study. At enrolment the subjects had a mean age of 45.0 months, a mean weight of 14.8 kg, a mean axillary temperature of 37.9°C and a geometric mean parasitaemia of 11,367 asexual stages/μl. About 55% of the children investigated were girls. There were no significant baseline difference between the two treatment arms. Although there was also no difference in the clearance of fever and parasitaemia between the two arms by day 14, a supervised child was significantly more likely to show an adequate clinical and parasitological response, by day 21 (91.3% v. 84.1%; P=0.05) or day 28 (80.0% v. 64.9%; P<0.01), than an unsupervised child. The reported adverse effects following treatment and the trend in haemoglobin recovery were, however, similar in the two arms. Although artesunate-amodiaquine appeared very effective in the treatment of uncomplicated P. falciparum malaria in children, whether supervised or not, it appears that supervised treatment provided stronger prevention against re-infection and recrudescence. At least in the present study, treatment at home, without medical supervision, probably led to relatively poor compliance. © 2008 The Liverpool School of Tropical Medicine.
Keywords: EMTREE drug terms: amodiaquine; artesunate